2015
DOI: 10.1016/j.cja.2014.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of blade sweep on inlet flow in axial compressor cascades

Abstract: This paper presents comparative numerical studies to investigate the effects of blade sweep on inlet flow in axial compressor cascades. A series of swept and straight cascades was modeled in order to obtain a general understanding of the inlet flow field that is induced by sweep. A computational fluid dynamics (CFD) package was used to simulate the cascades and obtain the required three-dimensional (3D) flow parameters. A circumferentially averaged method was introduced which provided the circumferential fluct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The findings further showed that there are two distinct stages in the stall evolution: the part span stall and the global stall correlated with the axisymmetric and asymmetric disruptions and the paper addressed the causes of these stalls. Chang et al [13] delved the influence of blade sweep in axial compressor cascades on inlet flow, and a sequence of sweeping and straight cascades was designed for this intent. The measurements are carried out with NUMECA International's finite-volume dependent Reynolds-Averaged Navier -Stokes FINE Turbo solver.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings further showed that there are two distinct stages in the stall evolution: the part span stall and the global stall correlated with the axisymmetric and asymmetric disruptions and the paper addressed the causes of these stalls. Chang et al [13] delved the influence of blade sweep in axial compressor cascades on inlet flow, and a sequence of sweeping and straight cascades was designed for this intent. The measurements are carried out with NUMECA International's finite-volume dependent Reynolds-Averaged Navier -Stokes FINE Turbo solver.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results indicate that blade sweep does affect inlet radial equilibrium, such as blade camber angles, solidity. Halder et al [21] researched an unswept blade and a 10 ∘ backward-swept blade, respectively. It was found that the backward-swept blade strongly affects the blade stall margin.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Compressor cascade is a simplified model of real axial compressor stator blade and has been widely applied to researching the mechanism and control of corner separation, as well as the compressor tip clearance flow structures and effects of threedimensional compressor blades. 12,13 Active flow control methods, such as boundary layer suction, [14][15][16] flow blowing, 17,18 plasma flow control 19,21 etc, have been applied to the control of compressor cascade corner separations over years. Meanwhile, the application of passive flow control methods, such as vortex generator, [22][23][24] endwall contouring 25 etc, as well as combination of passive and active control methods, 26 for corner separation control have been investigated with great efforts.…”
Section: Introductionmentioning
confidence: 99%